(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
For the satisfaction of hotel guests, the front desk is of the utmost importance. The workers working at the front desk have the most interaction with guests over the entirety of the guest life cycle. It is more probable that guests will return to the hotel or write a favourable review if the front desk operations crew creates a good impression on them. In other words, the success of the hotel is directly influenced by the front desk and its operations. The results of a number of polls indicate that the innovative approaches, service quality, politeness, competency, and responsiveness (CCR) of the staff members have a positive influence on the levels of customer satisfaction in the hotel. Employees working at the front desk are the face of the hotel and one of its most important divisions; thus, the performance of these employees is essential to the initial impressions that guests get of the establishment. There are a number of research findings that indicate that competence has a significant impact on a negative first impression, friendliness and service attitude have a significant impact on a positive first impression, and both positive and negative first impressions have a significant impact on the level of customer satisfaction with the check-in experience. It is hoped that the findings of this research would be of assistance in the development of future management training for workers who are new to the hotel industry.